Influence of wounding and temperature on resistance of maize landraces from Mexico to aflatoxin contamination - Ortega Beltran, A.; Cotty, P.J. (Frontiers Media, 2020)
Maize is a staple for billions across the globe. However, in tropical and sub-tropical regions, maize is frequently contaminated with aflatoxins by Aspergillus section Flavi fungi. There is an ongoing search for sources of aflatoxin resistance in maize to reduce continuous exposures of human populations to those dangerous mycotoxins. Large variability in susceptibility to aflatoxin contamination exists within maize germplasm. In Mexico, several maize landrace (MLR) accessions possess superior resistance to both Aspergillus infection and aflatoxin contamination but their mechanisms of resistance have not been reported. Influences of kernel integrity on resistance of four resistant and four susceptible MLR accessions were evaluated in laboratory assays. Wounds significantly (P < 0.05) increased susceptibility to aflatoxin contamination even when kernel viability was unaffected. Treatments supporting greater A. flavus reproduction did not (P > 0.05) proportionally support higher aflatoxin accumulation suggesting differential influences by some resistance factors between sporulation and aflatoxin biosynthesis. Physical barriers (i.e., wax and cuticle) prevented both aflatoxin accumulation and A. flavus sporulation in a highly resistant MLR accession. In addition, influence of temperature on aflatoxin contamination was evaluated in both viable and non-viable kernels of a resistant and a susceptible MLR accession, and a commercial hybrid. Both temperature and living embryo status influenced (P < 0.05) resistance to both aflatoxin accumulation and A. flavus sporulation. Lower sporulation on MLR accessions suggests their utilization would result in reduced speed of propagation and associated epidemic increases in disease both in the field and throughout storage. Results from the current study should encourage researchers across the globe to exploit the large potential that MLRs offer to breed for aflatoxin resistant maize. Furthermore, the studies provide support to the importance of resistance based on the living host and maintaining living status to reducing episodes of post-harvest contamination.